Chilling-injury reduction during the storage of tomato fruits by heat treatment with antioxidants - Прісс, Олеся Петрівна (Eastern-European Journal of Enterprise Technologies, 2015)
Despite the proven effectiveness of heat treatment and antioxidants, their combined effect for chilling-injury reduction during storage of tomato fruits has not been investigated. The influence of heat treatment with antioxidant compositions on the level and severity of chilling injury during storage of tomato fruits is considered in the paper. It was found that the chilling-injury rate of tomato fruits depends on the weather conditions during vegetation. There is the closest relationship with the hydrothermic coefficient of fruit development and ripening period(r=-0,79...-0,90) and the number of days, when the maximum temperature exceeds the biological maximum of the crop (r=0,76...0,90). Frequent temperature drops during the vegetation of tomatoes can result in could reduce susceptibility during storage, as evidenced by the inverse correlations with the chilling-injury level of tomato fruits. Using thermal treatment with complex antioxidant based on horseradish root extract, ionol and lecithin postpones the appearance of chilling symptoms by 3 weeks and reduces the percentage of injured fruits by 9,8...11 times compared with untreated tomato fruits and by 5.6...7.5 times compared with conventional heat treatment. Chilling index in experimental fruits, depending on the variety of tomato fruits and antioxidants is 7.0...14.7 times lower compared with the untreated fruits and by 3.3...7.7 times than in tomato fruits with water heat treatment.